Estudo de caso da implantação de controle de acesso seguro para as redes sem fio abertas na Universidade Federal do Pará - MOREIRA, Elder Thiago Costa (2019)
The Federal University of Pará as educational institution offers an open wireless network service to the visitors. However, in order to provide this service in an appropriated manner, some security measures are needed, aiming to avoid illicit virtual practices inside of the institutional domain. This study aims to present a proposal for reconstructing the wireless visitor network of the Federal University of Pará through to deployment and use of the PacketFence software, which manages the users’ access and devices in order to be possible to control and/or identify the access of the users of this network, adapting to the laws of the country. The absence of connection record and personal information is configured as incidents of imputability of information, so that the institution becomes responsible for any acts occurred inside of its network. Using this technological resource is possible to treat this particularity and then ensure those provided in the article of the law 12.965, from 23/04/2014, Civil Internet Framework or Regulatory internet framework.